Cleaner production and application in the Vietnam petroleum industry - Van Tuan Nguyen; Lan Huong Nguyen (Petrovietnam Journal, 2015)
Cleaner Production (CP) was first introduced in Vietnam in 1995 by the United Nations Environmental Programme (UNEP). According to UNEP, CP is the continuous application of an integrated preventive environmental strategy to processes, products, and services in order to increase efficiency and reduce risks to humans and the environment. The demonstration case studies have figured out that CP can give the opportunities to reduce from 10 - 15% of energy and input material consumption in production. CP brings about not only economic benefit but also environmental one to help improve production efficiency of both big and small companies.This paper introduces the concepts, methodology and benefits of Cleaner Production, its application and practice in the Vietnam National Oil and Gas Group.